Utility of Gram Staining for Evaluation of the Quality of Cystic Fibrosis Sputum Samples - Nair, Bindu (American Society for Microbiology, 2002)
The microscopic examination of Gram-stained sputum specimens is very helpful in the evaluation of patients with community-acquired pneumonia and has also been recommended for use in cystic fibrosis (CF) patients. This study was undertaken to evaluate that recommendation. One hundred one sputum samples from CF patients were cultured for gram-negative bacilli and examined by Gram staining for both sputum adequacy (using the quality [Q] score) and bacterial morphology. Subjective evaluation of adequacy was also performed and categorized. Based on Q score evaluation, 41% of the samples would have been rejected despite a subjective appearance of purulence. Only three of these rejected samples were culture negative for gram-negative CF pathogens. Correlation between culture results and quantitative Gram stain examination was also poor. These data suggest that subjective evaluation combined with comprehensive bacteriology is superior to Gram staining in identifying pathogens in CF sputum.